OPTIMALISASI KEAHLIAN TEKNIK BANGUNAN DI SMK DENGAN STRATEGI PEMBELAJARAN BLENDED LEARNING - Hanifa Khairunnisa (CV. ADIBA AISHA AMIRA, 2025)
Vocational Building Engineering Education plays a crucial role in producing skilled workforce required in the construction industry. In this digital era, traditional teaching methods are no longer adequate. This article discusses the implementation of blended learning strategy in electrical installation competency in Vocational High Schools (SMK). By combining online and face-to-face learning, students can engage flexibly and actively. Literature studies indicate that blended learning effectively enhances learning outcomes and critical thinking skills. Thus, this approach enables the optimization of building engineering skills in SMK